Women’s Entrepreneurship in the UAE: Exploring Cultural, Societal, and Structural Challenges through a Conceptual Lens - Alameeri, Khadija; Zakaria, Norhayati; Rahman, Syed Abidur (International Review of Management and Marketing, 2025)
This conceptual paper examines the complex influence of cultural, societal, and structural factors on women’s entrepreneurship in the United Arab Emirates (UAE). Drawing on existing literature, it develops a conceptual framework that captures how gender norms, social expectations, and institutional arrangements collectively shape the entrepreneurial pathways available to women. The paper contributes to the literature by moving beyond general accounts of barriers, focusing instead on the layered interactions between cultural systems and institutional support mechanisms. In addition to its theoretical contribution, the study outlines actionable strategies, including legal reforms, culturally responsive public messaging, and gender-sensitive financial and educational programs. These interventions aim to foster a more inclusive entrepreneurial environment that reflects the lived realities of women in the UAE and offers direction for future research and policy development.